Biology of human milk oligosaccharides: From basic science to clinical evidence. Issue 2 (2nd February 2022) - Sprenger, Norbert; Tytgat, Hanne L. P.; Binia, Aristea; Austin, Sean; Singhal, Atul
Abstract: Human milk oligosaccharides (HMOs) have been researched by scientists for over 100 years, driven by the substantial evidence for the nutritional and health benefits of mother's milk. Yet research has truly bloomed during the last decade, thanks to progress in biotechnology, which has allowed the production of large amounts of bona fide HMOs. The availability of HMOs has been particularly crucial for the renewed interest in HMO research because of the low abundance or even absence of HMOs in farmed animal milk. This interest is reflected in the increasing number of original research publications and reviews on HMOs. Here, we provide an overview and critical discussion on structure–function relations of HMOs that highlight why they are such interesting and important components of human milk. Clinical observations in breastfed infants backed by basic research from animal models provide guidance as to what physiological roles for HMOs are to be expected. From an evidence‐based nutrition viewpoint, we discuss the current data supporting the clinical relevance of specific HMOs based on randomised placebo‐controlled clinical intervention trials in formula‐fed infants. Abstract : An illustration of the human milk oligosaccharide (HMO) mediated microbiome–host interaction, highlighting its importance for the biology of HMOs for infant health. Key points: This review discusses different aspects of human milk oligosaccharides (HMOs): from their chemistry to biology. It provides a comprehensive overview of our current understanding of the clinical relevance of HMOs for infant development and health. Cumulative evidence from clinical observations and interventions backed by mechanistic basic research data indicates that HMOs are a meaningful and important component of human milk. Increasing evidence suggests that specific HMOs help establish immune competence, both local and systemically, partly through their effect on the metabolite activity of specific microbes mainly Bifidobacterium species. HMOs may also participate in a gut–brain connection, thereby modulating brain and cognitive development. HMOs likely act in concert with other bioactive components and act via different mechanisms that converge to specific functions.